Question
upstudy study bank question image url

Calculate the value of \( p \) if \( \sum_{k=0}^{\infty} 27 p^{k+1}=\sum_{r=3}^{14}(30-3 r) \)

Ask by Powell Summers. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( p = \frac{2}{3} \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

The Deep Dive

To solve for \( p \) in the given equation \( \sum_{k=0}^{\infty} 27 p^{k+1} = \sum_{r=3}^{14}(30-3r) \), we will start by simplifying each side of the equation. **Step 1: Simplifying the Left Side** The left side, \( \sum_{k=0}^{\infty} 27 p^{k+1} \), can be factored out as follows: \[ \sum_{k=0}^{\infty} 27 p^{k+1} = 27 p \sum_{k=0}^{\infty} p^k \] The series \( \sum_{k=0}^{\infty} p^k \) is a geometric series that converges if \( |p| < 1 \): \[ \sum_{k=0}^{\infty} p^k = \frac{1}{1-p} \] Thus, the left side becomes: \[ 27 p \cdot \frac{1}{1-p} = \frac{27p}{1-p} \] **Step 2: Simplifying the Right Side** Now we simplify the right side, \( \sum_{r=3}^{14}(30-3r) \). We can rewrite this as: \[ \sum_{r=3}^{14}(30-3r) = \sum_{r=3}^{14}30 - \sum_{r=3}^{14}3r \] Calculating \( \sum_{r=3}^{14}30 \): - There are \( 14 - 3 + 1 = 12 \) terms. \[ \sum_{r=3}^{14}30 = 30 \times 12 = 360 \] Now calculating \( \sum_{r=3}^{14}3r \): \[ \sum_{r=3}^{14}3r = 3 \sum_{r=3}^{14} r \] The sum \( \sum_{r=3}^{14} r \) is a series of integers from 3 to 14, which can be calculated as: \[ \sum_{r=3}^{14} r = \frac{n}{2}(a + l) \] where \( n \) is the number of terms, \( a \) is the first term, and \( l \) is the last term. - \( n = 14 - 3 + 1 = 12 \) - \( a = 3 \), \( l = 14 \) Calculating: \[ \sum_{r=3}^{14} r = \frac{12}{2}(3 + 14) = 6 \times 17 = 102 \] Thus, \[ \sum_{r=3}^{14}3r = 3 \times 102 = 306 \] Putting it all together on the right side, we have: \[ \sum_{r=3}^{14}(30-3r) = 360 - 306 = 54 \] **Step 3: Setting Both Sides Equal** Now, we set both expressions equal to each other: \[ \frac{27p}{1-p} = 54 \] **Step 4: Solving for \( p \)** Cross-multiplying gives: \[ 27p = 54(1-p) \] Simplifying further: \[ 27p = 54 - 54p \] Combining like terms: \[ 27p + 54p = 54 \] This simplifies to: \[ 81p = 54 \] Dividing both sides by 81 results in: \[ p = \frac{54}{81} = \frac{2}{3} \] Thus, the value of \( p \) is: \[ \boxed{\frac{2}{3}} \]

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy